Almost Periodic Solution of a Discrete Commensalism System. (22nd October 2015) - Xue, Yalong; Xie, Xiangdong; Chen, Fengde; Han, Rongyu
Abstract : A nonautonomous discrete two-species Lotka-Volterra commensalism system with delays is considered in this paper. Based on the discrete comparison theorem, the permanence of the system is obtained. Then, by constructing a new discrete Lyapunov functional, a set of sufficient conditions which guarantee the system global attractivity are obtained. If the coefficients are almost periodic, there exists an almost periodic solution and the almost periodic solution is globally attractive.